2024
DOI: 10.1371/journal.pone.0298000
|View full text |Cite
|
Sign up to set email alerts
|

Intervention and assessment of executive dysfunction in patients with stroke: A scoping review

Katsuya Sakai,
Yuichiro Hosoi,
Junpei Tanabe

Abstract: Rehabilitation methods for executive dysfunction were focused on cognitive rehabilitation in patients with stroke and traumatic brain injury. However, no reviews have focused on the various rehabilitation methods and assessment of executive function in patients with only stroke and included various study designs. This study aimed to identify various interventions and assessments in patients with stroke and executive dysfunction via a scoping review. We searched for articles using the PubMed, Web of Science, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…S. Hayes et al (2016) investigated the association between executive dysfunction and balance in patients with stroke and reported that a factor associated with executive dysfunction was balance function as measured by the BBS. Executive functions include goal planning, task implementation, flexible thinking, and working memory (Sakai et al, 2024;Skidmore et al, 2023). TUGT requires goal planning and task execution as well as other executive functions such as getting up from a chair, walking around a cone, and sitting in a chair again (Hafsteinsdottir et al, 2014).…”
Section: Regarding Executive Dysfunction and Balance Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Hayes et al (2016) investigated the association between executive dysfunction and balance in patients with stroke and reported that a factor associated with executive dysfunction was balance function as measured by the BBS. Executive functions include goal planning, task implementation, flexible thinking, and working memory (Sakai et al, 2024;Skidmore et al, 2023). TUGT requires goal planning and task execution as well as other executive functions such as getting up from a chair, walking around a cone, and sitting in a chair again (Hafsteinsdottir et al, 2014).…”
Section: Regarding Executive Dysfunction and Balance Functionmentioning
confidence: 99%
“…In TMT part B, participants connected numbers and letters alternately in sequence as fast as possible (Reitan & Wolfson, 1985;Tamez et al, 2011). In this study, TMT part B was used as an indicator of executive dysfunction (Sakai et al, 2023(Sakai et al, , 2024.…”
Section: Executive Function and Cognitive Assessmentsmentioning
confidence: 99%